A novel hybrid evolutionary data-intelligence algorithm for irrigation and power production management: Application to multi-purpose reservoir systems - Yaseen Z.M.; Ehteram M.; Hossain M.S.; Fai C.M.; Koting S.B.; Mohd N.S.; Jaafar W.Z.B.; Afan H.A.; Hin L.S.; Zaini N.; Ahmed A.N.; El-Shafie A. (MDPI, 2023)
algorithm; artificial intelligence; comparative study; decision making; evolutionary theory; expert system; irrigation; management practice; methodology; numerical model; power generation; reservoir; water management; water resource; India; Karnataka; Chondrichthyes